Analysis of S‐allele genetic diversity in Sicilian almond germplasm comparing different molecular methods. Issue 6 (16th October 2015) - Currò, Sergio; La Malfa, Stefano; Distefano, Gaetano; Long, Guiyou; Sottile, Francesco; Gentile, Alessandra
Abstract: Italian almond germplasm is characterized by a wide diversity in several growing areas among which Sicily is one of the most important. Analysis with consensus and specific primers and DNA sequencing was performed to investigate S‐RNase genetic diversity and to elucidate the homology rate within a genetic pool of 27 Italian accessions. Interestingly, some of the self‐compatible cultivars did not show the presence of S f allele. Amplicons from consensus and allele‐specific PCR primers revealed a high level of variability. Sequencing of all the S‐RNase amplicons derived from consensus primers allowed the identification of two new S‐RNase alleles ( S 51 and S 52 ). Surprisingly, despite the AA replacement mutation, S 51 did not exhibit any change of its S‐RNase function. Additionally, several mutations, with no effect on amino acid composition, were detected in the intron and/or in the ORF of four known alleles ( S g, S 10, S 31 and S 35 ). Genetic variation, regarding point mutations and only detected by sequencing, was revealed among 11 of 27 tested cultivars. The new sources of variability might have an interest for product traceability.